Understanding the Enhanced Separation Mechanism of C2H4/C2H6 at Low Pressure by HKUST−1 - Wenpeng Xie; Qiuju Fu; Xiangjun Kong; Xiangsen Yuan; Lingzhi Yang; Liting Yan; Xuebo Zhao (Chemistry, 2024)
The production of ethylene (C2H4) is typically accompanied by the formation of impurities like ethane (C2H6), making the separation of C2H4 and C2H6 crucial in industrial processes. Here, we investigated the S-shaped adsorption phenomenon of C2H6 on the metal–organic framework HKUST−1. The virial equation is used to fit the C2H6 and C2H4 adsorption isotherms under low coverage. The results showed that the repulsion energy between neighboring C2H6 molecules was significantly higher than that between neighboring C2H4 molecules, which was an important reason for the lower adsorption of C2H6 by HKUST−1 at low coverage. As more molecules are adsorbed, gas molecules aggregate within pores, leading to more hydrogen bonds formed between HKUST−1 and larger-sized C2H6 under high coverage conditions. This phenomenon plays a crucial role in the S-shaped adsorption behavior of HKUST−1 on C2H6. Additionally, this unique adsorption behavior allows for the efficient separation of C2H4/C2H6 mixtures at low pressures. The ideal adsorbed solution theory (IAST) selectivity of HKUST−1 for C2H4/C2H6 mixtures was 3.78 at 283 K and 1 bar, but increased significantly to 7.53 under low pressure. This unique mechanism provides a theoretical basis for the low-pressure separation of C2H4/C2H6 by HKUST−1 and establishes a solid foundation for future practical research applications.